2020
DOI: 10.1007/s40615-020-00833-4
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Economic, and Health Inequality and COVID-19 Infection in the United States

Abstract: Objectives There is preliminary evidence of racial and social economic disparities in the population infected by and dying from COVID-19. The goal of this study is to report the associations of COVID-19 with respect to race, health, and economic inequality in the United States. Methods We performed an ecological study of the associations between infection and mortality rate of COVID-19 and demographic, socioeconomic, and mobility variables from 369 counties (total population, 102,178,117 [median, 73,447; IQR, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
428
4
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(520 citation statements)
references
References 21 publications
30
428
4
13
Order By: Relevance
“…Finally, families with a relatively higher socio-economic status reported greater medical provider stress and child-reports of positive life events. These ndings parallel reported disparities in COVID-19 exposures and impact in the literature, with greater negative stress for racial/ethnic minority families and more protective factors for families with greater socio-economic resources (Abedi et al, 2020) even within this relatively privileged sample.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Finally, families with a relatively higher socio-economic status reported greater medical provider stress and child-reports of positive life events. These ndings parallel reported disparities in COVID-19 exposures and impact in the literature, with greater negative stress for racial/ethnic minority families and more protective factors for families with greater socio-economic resources (Abedi et al, 2020) even within this relatively privileged sample.…”
Section: Discussionsupporting
confidence: 78%
“…Limitations include the presence of only two time points, inclusion of a single parental perspective (often mothers) and no siblings, and restricted diversity in the sample. This last point is particularly important given that the pandemic has disproportionately impacted racial/ethnic minority families and low socio-economic families (Abedi et al, 2020). Understanding how the pandemic has impacted a wide range of families, both within the US and across the globe, will be critical in supporting the developmental recovery of youth and their families in the years to come.…”
Section: Limitationsmentioning
confidence: 99%
“…Hispanics and Blacks were the largest group living in hotspot counties [21]. Abedi et al [30] found that Blacks were more vulnerable to COVID-19 than other racial and ethnic groups. Table 4 summarizes values of the HCR by race and ethnicity.…”
Section: Deprivation By Race and Ethnicitymentioning
confidence: 99%
“…Digital technologies have taken the center stage in the response to COVID-19 12 , and mobility data in particular has allowed to assess the response to nonpharmaceutical interventions 13,14 .Previous studies report large scale reductions in movements, with numbers quickly reaching values typically observed during holiday periods 9 . Furthermore, in the United States, changes in mobility were associated with reductions in COVID-19 cases 15,16 and in the reproduction number 17 and mobility data also revealed that the changes were largely already underway when state or county stay-at-home orders were issued 15,18,19 .…”
Section: Introductionmentioning
confidence: 98%